PENGARUH TOUR EXPERIENCE TERHADAP BEHAVIORAL INTENTIONS DI JENDELA ALAM BANDUNG - Ronaldi Pram Agusti, - (2019)
The purpose of this research are: 1) to analyse tour experience at Jendela Alam Bandung, 2) to analyse behavioral intentions at Jendela Alam Bandung, 3) to analyse the effect of tour experience on behavioral intentions at Jendela Alam Bandung. The method of this analysis used is descriptive verifikatif and multiple regression. Data obtained through questionnaires where distributed directly and also online using google form and spread by providing link from google form through Line, WhatsApp, TripAdvisor, and Instagram to visitors who have visited as many as 200 respondents. Based on the results, obtained multiple regression results are simultaneously, tour experience has a significant influence on the behavioral intentions at Jendela Alam Bandung. However, partially mentioned that sub variable entertainment, educational, and escapism are significant effect on behavioral intentions. The entertainment sub variable has the highest value, while the lowest value is in the sub variable of esthetic assessment. Keywords: tour experience, behavioral intentions.